The grow of seaweeds (Eucheuma cottonii) in different initial weight at Pandawa Beach, Bali - Antari, Ni Pande Putu Suji Dian; Watiniasih, Ni Luh; Dewi, Ayu Putu Wiweka Krisna (Jurnal Biologi Udayana, 2021)
Seaweed is a low-level plant, does not have exact roots, stems, and leaves, and the plant part is called the thallus. One species that is often cultivated by the seaweed farmers in Bali is Eucheuma cottonii . The initial weight of the seeds planted can affect the growth of seaweed. The results of the study found that good seaweed seeds used ranged from 50-150 g, but has never been studied in detail on E. cottonii using floating raft method. This study aims to determine the initial weight of seaweed seeds that are good for growth using the floating raft method where the seeds are placed in a bag. This study consisted of 3 treatments, namely treatment A with a seed weight of 50 g, treatment B with a seed weight of 100 g, and treatment C with a seed weight of 150 g. This research was conducted at Pandawa Beach, Bali, from March-April 2021, which data was collected once a week for 7 weeks. The results showed that the growth of seaweed increased every week and different between treatments. The final weight of seaweed in treatment A was 558.83 g, treatment B was 552.167 g, and treatment C was 529.67 g. Seaweed growth in treatment A was higher than treatment B and C. The average Specific Growth Rate (SGR) in treatment A was 4.92%, treatment B was 3.48%, and treatment C was 2.57%. The best results from the seeds used were found in seedlings with an initial weight of 50g, compared to the weight of other seeds (P<0.002).